Rural youth and folklore in conflict: The case of The Bagpipe dance from Cervera del Río Alhama (La Rioja) - Rubio Gil, María Ángeles; Vázquez Vicente, Guillermo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In the rural dances of north of Spain, reminiscences of a pagan nature can be verified. Endowed with strong sacred connotations, their prevalence, and the interest of youth in high schools, surprises in a secular, individualistic and hyper-rational environment. This is the interest to understand the intergenerational conflicts that have arisen today, through the study of the case of ‘La Gaita de Cervera del Río Alhama’ (La Rioja). A dance that was considered atrial and that is, however, a set of sacred fertility rites, adapted with the same vocation as a community, petition and transit rite.